Keterampilan Berbicara (Sprechfertigkeit) Bahasa Jerman Melalui Metode Gruppenarbeit - Orinyundi Pasu; Jufri Jufri; Misnawaty Usman (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. The purpose of this study was to determine the improvement of speaking skills of class X IBB SMAN 5 Tana Toraja students through the application of the Gruppenarbeit method. the type of research used is classroom action research.  This research consisted of two cycles, each cycle consisting of the planning stage, implementation stage, observation stage, and reflection stage. research subjects were students of class X IBB SMAN 5 Tana Toraja, as many as 34 students.  the results of data analysis showed that the German speaking skill with the score obtained by the students in the first cycle was 56% and the second cycle 80%. From the data from this research, it can be concluded that the use of the Gruppenarbeit method can improve the German speaking skills of class X IBB SMAN 5 Tana Toraja students. Keywords: Classroom Action Research, Speaking Skills, Gruppenarbeit Method.